Fast gated EPR imaging of the beating heart: Spatiotemporally resolved 3D imaging of free‐radical distribution during the cardiac cycle. Issue 2 (3rd April 2012) - Chen, Zhiyu; Reyes, Levy A.; Johnson, David H.; Velayutham, Murugesan; Yang, Changjun; Samouilov, Alexandre; Zweier, Jay L.
Abstract In vivo or ex vivo electron paramagnetic resonance imaging (EPRI) is a powerful technique for determining the spatial distribution of free radicals and other paramagnetic species in living organs and tissues. However, applications of EPRI have been limited by long projection acquisition times and the consequent fact that rapid gated EPRI was not possible. Hence in vivo EPRI typically provided only time‐averaged information. In order to achieve direct gated EPRI, a fast EPR acquisition scheme was developed to decrease EPR projection acquisition time down to 10–20 ms, along with corresponding software and instrumentation to achieve fast gated EPRI of the isolated beating heart with submillimeter spatial resolution in as little as 2–3 min. Reconstructed images display temporal and spatial variations of the free‐radical distribution, anatomical structure, and contractile function within the rat heart during the cardiac cycle. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.